Spatial variation, bias and experimental design in agronomic field trials: a case study of a farming systems trial in the Western Cape province, South Africa - Osborne, Devin Guy (Stellenbosch : Stellenbosch University, 2017)
Thesis (MScAgric)--Stellenbosch University, 2017.